Cinema Architecture in Spain : from Pavillons to Movie Palaces - Lavilla Iribarren, Ana Cristina (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2018)
This text analyzes some elements that have characterized the architecture designed for cinematographic exploitation in Spain during the first decades of evolution of the show. Given the social, economic and cultural transformations that occurred simultaneously with the rise of “cinematographic representations” in fairs and later in many types of pavilions, this article aims to draw up an assessment of the evolution experienced by these spaces, and having led to the creation of a true architectural typology inspired by theatrical architecture. For this, this analysis is based on the study of some typologies developed particularly in the 1920s in Spain, while examining the projects of two leaders in the field of architecture for cinema: Teodoro Anasagasti and Luis Gutiérrez Soto. As for the buildings of Anasagasti, one will find mainly the presence of a “Beaux-Arts style”; and those of Gutiérrez Soto, we will rather see a spirit of avant-garde accompanied by a rationalism still emerging in Spain at that time.